Elaboración de un sistema de compras de insumos médicos y medicinas para el área de salud n. 5 de la mana provincia de Cotopaxi 2010 - Jacho Machimba, Nelson Roberto (2012)
The purpose of designing a system of medical supply purchases and medicine for the Health Area No. 5. is to help the administration and its collaborators with the establishment of a set of rules and procedures to achieve efficient and effective use of resources by not having a shopping system, it causes the processes are carried out mostly with inadequate management of procurement and no description of the method of control, they headed for the institution to an undesirable future. Is a feasible project and is supported by a theoretical basis, in turn uses the descriptive research, and has an experimental methodology in which we work with interviews and surveys with officials of the entity health sector entities that have no a purchasing system, run the risk of presenting deviations in their procedures, and certainly no decisions will be most appropriate for their management and even could lead to an operational crisis, to be viable the implementation of the system are described processes for different activities....